PRECISION AND VAGUENESS IN THE LANGUAGE OF THE LAW IN HUNGARIAN AND POLISH LEGAL TEXTS - KACZMAREK, Karolina (Comparative Legilinguistics, 2013)
The article discusses two issues connected with the philosophy of law. On the one hand, the law should be formulated in a general way, because it must be applicable in many relevant situations. On the other, it should be precise, because people should be aware exactly of what they can do and what is forbidden to them. In the article the author points out such features of law and language which influence a text to help formulate and interpret it in a particular way that meets both criteria: to be vague and yet enough precise. In the first part, the article points out some kinds of interpretation in law which are especially closely connected with language level. In the second part, the author discusses such features of language which are important when we interpret those texts which are legal, especially the semantic meaning of some vague expressions. In the third part the author points out such language features which may help to make a text more precise, such as definitions, context and other ways of making terms more precise. In the last section the author points out some vague expression grouped grammatically. As the base of her empirical research the author has used Polish and Hungarian legal texts.